Stable knockdown of Drp1 improves retinoic acid-BDNF-induced neuronal differentiation through global transcriptomic changes and results in reduced phosphorylation of ERK1/2 independently of DUSP1 and 6 - Ghani, Marvi; Zohar, Peleg; Ujlaki, Gyula; Tóth, Melinda; Amsalu, Hailemariam; Póliska, Szilárd; Tar, Krisztina (Frontiers in Cell and Developmental Biology, 2024)
Background: Dynamin-related protein Drp1 —a major mitochondrial fission protein— is widely distributed in the central nervous system and plays a crucial role in regulating mitochondrial dynamics, specifically mitochondrial fission and the organelle's shaping. Upregulated Drp1 function may contribute to the pathological progression of neurodegenerative diseases by dysregulating mitochondrial fission/ fusion. The study aims to investigate the effects of Drp1 on retinoic acid-BDNF-induced (RA-BDNF) neuronal differentiation and mitochondrial network reorganization in SH-SY5Y neuroblastoma cells. Methods: We generated an SH-SY5Y cell line with stably depleted Drp1 (shDrp1). We applied RNA sequencing and analysis to study changes in gene expression upon stable Drp1 knockdown. We visualized the mitochondria by transmission electron microscopy and used high-content confocal imaging to characterize and analyze cell morphology changes and mitochondrial network reorganization during neuronal differentiation. Results: shDrp1 cells exhibited fused mitochondrial ultrastructure with perinuclear clustering. Stable knockdown of Drp1 resulted in the upregulation of genes involved in nervous system development. High content analysis showed improved neurite outgrowth, segmentation, and extremities in differentiated shDrp1 cells. Neuronal differentiation was associated with a significant reduction in ERK1/2 phosphorylation, and ERK1/2 phosphorylation was independent of the dual specificity phosphatases DUSP1/6 in shDrp1 cells. Differentiated control underwent mitochondrial morphology remodeling, whereas differentiated shDrp1 cells retained the highly fused mitochondria and developed long, elongated structures. The shDrp1 cells responded to specific apoptotic stimuli like control in vitro, suggesting that Drp1 is not a prerequisite for apoptosis in SH-SY5Y cells. Moreover, Drp1 downregulation reduced the formation of toxic mHtt aggregates in vitro. Discussion: Our results indicate that Drp1 silencing enhances RA-BDNF-induced neuronal differentiation by promoting transcriptional and mitochondrial network changes in undifferentiated cells. We also demonstrate that the suppression of Drp1 reduces toxic mHtt aggregate formation in vitro, suggesting protection against neurotoxicity. Thus, Drp1 may be an attractive target for further investigation in future strategies to combat neurodegenerative diseases.